Heatwave-protective knowledge and behaviour among urban populations: a multi-country study in Tunisia, Georgia and Israel - Joris Adriaan Frank van Loenhout; Kirsten Vanderplanken; Tamari Kashibadze; Nia Giuashvili; Amiran Gamkrelidze; Maya Siman-Tov; Bruria Adini; Debarati Guha-Sapir (BMC, 2021)
Abstract Background There is an expected increase in heatwaves globally. As such, it is imperative to have sufficient levels of heatwave-protective knowledge and behaviour in areas regularly affected by heatwaves. Our study assessed this among urban populations in Tunisia, Georgia and Israel. Methods We undertook a cross-sectional population survey in the three countries. The questionnaire focused on obtaining information on respondents' knowledge level regarding 1) symptoms due to overheating, 2) risk groups for heatwaves, 3) actions to take when someone is overheated, and 4) heatwave-protective measures. Furthermore, we asked respondents about protective measures they applied during the last heatwave. We compared the results between the countries. Results Heatwave-protective knowledge was highest in Israel, and lowest in Georgia, for all indicators except for heatwave-protective measures, for which knowledge was highest in Tunisia. Most respondents who named certain protective measures had also applied these during the last heatwave: more than 90% for all measures except for one in Tunisia and Israel, and more than 80% for all measures in Georgia. Conclusion There is a need to further improve heatwave-protective knowledge in Tunisia, Georgia and Israel. One potential solution to achieve this is by implementing a National Heat Health Action Plan. Improving knowledge is a vital step before adaptive behaviour can take place.